PEMBERDAYAAN KELOMPOK WANITA TANI DALAM PEMANFAATAN SAMPAH ORGANIK RUMAH TANGGA MENGGUNAKAN TRICHODERMA SPP DI DESA BONGOHULAWA KABUPATEN BONE BOLANGO - Pulogu, Siska Irhamnawati; Iswati, Rida; Dama, Hasna; Isami, Delvira; Lamatenggo, Reska (Jurnal Abdi Insani, 2024)
The Women Farmers Group or KWT is part of the agricultural community group. KWT needs to be empowered to process household waste generated from daily activities. The use of the Trichoderma sp fungus in breaking down organic waste into organic fertilizer in the form of compost. Empowering KWT in processing household waste using Trichoderma spp into compost is one way to support sustainable and environmentally friendly agricultural activities. The aim of this activity is to provide training and practice in processing household organic waste using Trichoderma spp in Bongohulawa village. The methods include counseling, discussions with the participants and followed by a KWT demonstration in processing household organic waste to make organic fertilizer/compost. KWT Mawar participants responded very enthusiastically to the implementation of service activities because of the material and training on the use of household organic waste using the Trichoderma sp fungus is something new for this community group. Demonstration activities produced samples of wet organic waste and dry waste which were stored in sacks and tightly closed for 4 weeks. The results of processing household organic waste are characterized by changes in the texture of the waste which has been crushed and has a blackish brown color. The success of the household waste decomposing household waste into trichocompost certainly motivates every KWT member to adopt a household waste processing using Trichoderma spp to produce trichocompost.